Dietary habits of the brown bear (Ursus arctos) in the transboundary Prespa basin - Gonev, Andrej; Pavlov, Aleksandar; Lama, Olsion; Alexandrou, Olga; Henderson, Julia; Hoxha, Bledi; Melovski, Dime; Shyti, Ilir; Stojanov, Aleksandar; Trajçe, Aleksandër; Catsadorakis, Giorgos (Macedonian Journal of Ecology and Environment, 2023)
Proper conservation of large carnivores always entails a robust understanding of their ecology. The diet is one of the fundamental elements that needs to be well assessed before proposing sound management measures. The brown bear population in Prespa is shared among three countries – Albania, Greece and North Macedonia – that considerably vary in habitat complexity and the human practices taking place. Therefore, a comprehensive evaluation of the bear’s dietary habits is essential to minimize potential human-bear conflicts. To that aim, a total of 553 samples were collected from 22 different habitats in all three countries. The results indicate that the diet of bears greatly depends on fruiting plants, with cherry plums (Prunus cerasifera) present in nearly half of the samples. The seasonal availability of fruits and plants also plays a crucial role, where grasses and early bloomers, like wild cherries, are more dominant in spring, cherry plums in summer, while apples and hardy masts, like acorns, predominate in autumn. In addition, results show that predation and scavenging play an insignificant role in the diet of this subpopulation of bears, with mammal remains detected in 4.7% of the samples, and only 1.45% of which belong to livestock, rendering the bear a less likely threat to livestock farming in the area. One cannot exclude the potential threat bears pose to agricultural activities, although its extent is still unknown. Thus, future conservation and management plans in Prespa should consider the dietary habits and habitat preferences of the brown bear.